RELIGIOUS VALUES AND INDUSTRIAL DEVELOPMENT IN VICTORIAN AGE AS RFLECTED IN NOVEL BRAM STOKER‟S DRACULA - Sastika Seli (Jurnal Perspektif Pendidikan, 2015)
The research aims to reveal the relationship between religious values and industrial development in Victorian age as reflected in novel Bram Stoker’s Dracula. The sociological approach was used to analyze the social aspects as reflected in the novel. There are two major concerns in the research; they are religious values and industrial development. The findings show that there are two kinds of relationships between the two aspects, namely, positive relationship and negative relationship. In a positive way, people still were able to maintained the religious values inside their selves, for instance, as reflected by the main character Jonathan Harker. Therefore, their religious values were useful to be a shield in revolutionary revolution. On the contrary, in a negative way, the religious values of society were decreasing along with the development of industry which also influenced many aspects in their lives.